2012
DOI: 10.2319/112211-725.1
|View full text |Cite
|
Sign up to set email alerts
|

Condyle fossa relationship associated with functional posterior crossbite, before and after rapid maxillary expansion

Abstract: Objective: To investigate condylar symmetry and condyle fossa relationships in subjects with functional posterior crossbite comparing findings before and after rapid maxillary expansion (RME) treatment through low-dose computed tomography (CT). Materials and Methods: Twenty-six patients (14 girls and 12 boys, mean age 9.6 6 1.4 years) with functional posterior crossbite (FPXB) diagnosis underwent rapid palatal expansion with a Hyrax appliance. Patients' temporomandibular joints (TMJ) underwent multislice CT sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 27 publications
4
52
2
3
Order By: Relevance
“…The findings of the present study are of paramount importance because previous studies that have evaluated condylar spaces using CBCT images are limited (11,13,14,21). When the sagittal image was being constructed, the long axis of the condyle was selected as the line passing through the central aspect of the condyle.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The findings of the present study are of paramount importance because previous studies that have evaluated condylar spaces using CBCT images are limited (11,13,14,21). When the sagittal image was being constructed, the long axis of the condyle was selected as the line passing through the central aspect of the condyle.…”
Section: Discussionmentioning
confidence: 77%
“…The following cephalometric measurements were obtained for determining the groups: sella-nasion-A point angle (SNA°), sella-nasion-B point angle (SNB°), A point-nasion-B point angle (ANB°), Frankfurt horizontal- mandibular plane angle (FMA°), lower facial height angle (LFH°), upper incisor- Frankfurt horizontal angle (U1-FH°), overjet (mm), and overbite (mm). For temporomandibular joint measurements, the CBCT images were saved as DICOM files, and processed using the OsiriX medical imaging software program (Open-Source, OsiriX Medical Imaging Software, www.osirix-viewer.com), as previously described by Leonardi et al (14) The long axis, which was defined as the line passing through the midline of the condyle in the coronal and axial sections was determined and the sagittal image was constructed.…”
Section: Methodsmentioning
confidence: 99%
“…Also, an anterior/inferior distraction and medial position of the condyle of the noncrossbite side and a posterior/superior (compression) and lateral position on the crossbite side have been described. 15 However, no significant differences in condyle position within the glenoid fossa have been reported, 21 nor was there a noticeable mandibular functional shift in untreated adult patients with PUXB. 11 These findings further corroborate the adaptive nature of the glenoid fossa even in PUXB patients, which is known to occur after changes in the occlusion and positioning of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…The findings explained why the location of both condyle heads (crossbite and noncrossbite sides) within the glenoid fossa have been reported as similar and not deviating from normal. 6,14,21 Thus, the original lateral displacement of the mandible must have been compensated with TMJ complex adaptive remodeling of the condyles, glenoid fossae, or a combination of these factors. 6 This condition raises the question of PUXB correction in adult patients by orthodontic means alone, which might lead to a sudden change in the function of the mandibular condyles.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, mandibular shift might occur thus reducing the positional crossbite after RME. Previous studies [32] suggested small amount of changes in condylar position in patients presenting functional posterior crossbite and undergone RME. Moreover, the lack of a control untreated group, mainly for ethical reasons, also limits most of these studies.…”
Section: Discussionmentioning
confidence: 99%